METABOLIC SYNDROME IN OBSTETRICS AND GYNECOLOGY - Taqiyeva, F. (World of Medicine and Biology, 2016)
Along with metabolic syndrome pregnancy, childbirth, the postpartum period occur with a significant number of complications. Analysis of available information about pregnancy in terms of metabolic syndrome, suggests that the accession of preeclampsia is in the first place in the structure of gestational complications in 60-100% of cases. Gynecological pathology, which is characterized by the development of metabolic syndrome includes hyperplasia and endometrial cancer, the syndrome of hyperandrogenism, endometriosis, dishormonal breast disease, menopausal metabolic syndrome, etc. Given the importance of this problem in obstetrics is the actual creation of the program pregravid preparation and management of patients with metabolic syndrome at all stages of gestation.
Keywords: metabolic syndrome; obesity; pregnancy; complications; menopause